Is ride-hailing competing or complementing public transport? A perspective from affordability. (January 2023) - Qiao, Si; Gar-On Yeh, Anthony
Abstract: To formulate policies for low-carbon transport development, previous studies largely focus on estimating the substitution effect of ride-hailing travel on public transport, but how transit-dependent people turn to use ride-hailing has not been answered. This study integrates small data (questionnaire) and big data (ride-hailing orders) to estimate how many ride-hailing trips could have been made via public transport from a perspective of affordability. The findings indicate that ride-hailing is competing with meanwhile complementing public transit, but for different purposes and target populations. Results show that 38% of ride-hailing trips can be potentially travelled via public transit at an overall level. But for commuting purpose, the proportion increased to 80%. For entertainment travel purposes, low-income families who could not afford private cars in the past, use ride-hailing as a flexible travel alternative, like what has been enjoyed by higher-income families.